(untitled) (Estudios Gerenciales, 2004)
An analysis was made of then effectof the Tender Offer Law in Chile, andof the related situation of five countrieswith a more developed marketthan the Chilean one, reaching theconclusion that in order to successfullyimplement a Tender Offer Lawit is necessary to bear in mind thatthe problem is not solved by establishingstandards that regulate transactions,but by creating instancesthat contribute to a more dynamicand efficient market. In addition,there should exist a balance betweenprotection of the minority stockholderand competition for corporate control.Finally, we can conclude that thereis evidence that the Tender Offer Lawhas depressed the Stock Exchange.